Assessing the Damages and Challenges of the Iranian Banking System from the Perspective of Islamic Economics in order to Realize Islamic Banking - Gholam-Hossein Malekloo , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A country's banking system is one of the most important pillars of its economy, and as long as this system is coherent, robust and flawless, it will equally enhance and strengthen the country's economic base. Changing the banking system of the country, and eliminating usury (Riba) from the monetary body of the country's economic system was one of the issues that attracted the attention of the legislative and executive authorities following the victory of the Islamic revolution of Iran. Since the banking system of an Islamic country requires good compliance with Islamic law and sharia, compliance with the performance of Islamic banking indicators in an Islamic-oriented economy will be essential. There have been various developments in Iran since the victory of the Islamic revolution, and one of these developments has been the debate on Islamic banking without usury. Although a number of steps have been taken in this regard, there has been no comprehensive measurement to Islamize complement the country's banking system, and this has been due to various problems along this way. In this article, while examining the current state of Iran's banking in general, the indicators of an Islamic banking system are examined in relation to some of the most successful examples in the world, and while assessing the problems and challenges of fully implementing Islamic banking in Iran, some strategies will be provided for this purpose.